Characterization of the Mitochondrial Plasmodium falciparum heat shock protein 70 - Nyakundi, David Onchong'a (Rhodes University, Faculty of Science, Biotechnology Innovation Centre, 2017)
Malaria remains a global health problem and accounts for many deaths and illnesses in subSaharan Africa. Plasmodium falciparum, the causative agent of the most fatal form of malaria, expresses a repertoire of heat shock proteins for cytoprotection, survival and pathogenesis. The parasite genome encodes six Hsp70 proteins found in various cell compartments. However, the putative parasite mitochondrial Hsp70 (PfHsp70-3) has not been investigated. The J-proteins, Pfj1 and PFF1415c, were proposed to function as co-chaperones of PfHsp70-3. The biochemical characterization of PfHsp70-3 was initially complicated by the fact that the protein was insoluble when expressed in E. coli cells. Various approaches to solubilize it resulted in inactive protein. A general characteristic of eukaryotic mitochondrial Hsp70s is their insolubility and their reliance on an Hsp70 escort protein (Hep) for solubility and ultimate functions. In this study, a putative Hep protein was identified in the genome of P. falciparum that is referred to as PfHep1. Coexpression of PfHep1 with PfHsp70-3 resulted in soluble and biochemically active PfHsp70-3. Size exclusion chromatography was employed to separate PfHsp70-3 from PfHep1 after coexpression. PfHep1 suppressed thermally induced aggregation of PfHsp70-3 but not the aggregation of malate dehydrogenase or citrate synthase, thus showing specificity for PfHsp70-3. Zinc ions were also found to be essential for maintaining the functions of PfHep1, as EDTA chelation abrogated its abilities to suppress the aggregation of PfHsp70-3. Furthermore, PfHep1 did not stimulate the basal ATPase or increase refoldase activities of PfHsp70-3 hence displaying no co-chaperone roles. The full-length putative mitochondrial type I J protein, Pfj1, could not be produced in E.coli but a truncated protein containing the J-domain was produced which stimulated both the ATPase and refoldase activities of PfHsp70-3. Further, this study demonstrated that both PfHep1 and PfHsp70-3 localized to the mitochondrion in the erythrocytic stage of P. falciparum development thus confirming in silico predictions of their localization. Besides, PfHsp70-3 was expressed during all stages of the intraerythrocytic cycle of parasite development and was heat inducible. Generally, the data obtained in this study will enhance the existing knowledge on the biology of the parasite mitochondrial chaperone functions and open the possible avenue of drug targeting considering the specificity of PfHsp70- 3 and PfHep1 partnerships.
Keywords: Uncatalogued